Surviving adolescent cancer: Narratives of disruption and identity reconstruction - Ntali, Evdokia; Stavropoulos, Konstantinos (Psychology: the Journal of the Hellenic Psychological Society, 2025)
The present qualitative study adopted a narrative approach to explore the experiences of young adult survivors who had been diagnosed with cancer during adolescence. We conducted 24 narrative interviews with eight survivors aged between 18 and 25 years old - three interviews with each one of them. The participants’ stories were analyzed through a thematic narrative analysis and the main thematic units that emerged are: (a) dealing with a fragile body, (b) renegotiating lost time, and (c) making meaning of illness. The participants’ narratives indicate that experiencing cancer during adolescence triggers a rupture in terms of the continuity of temporality. Thus, the identity of survivors is woven around the experience of the illness and is mediated by a long course of challenges–both during the disease, as well as returning to a state of "normality". A common theme of the narratives is the approach of illness as an experience that activates inner forces and leads to the construction of a new meaning in life, along with the creation of a new identity. The findings can inform clinical practitioners highlighting the need to approach cancer not as a life event that is time-limited and ends with the completion of treatment, but as a condition leading survivors to the need for negotiation of pain, body image, relationships and the identity as a whole.